RESPON MASYARAKAT TERHADAP KEGIATAN PENYULUHAN KEHUTANAN DI DESA SIBALAYA UTARA KECAMATAN TANAMBULAVA KABUPATEN SIGI SULAWESI TENGAH - Rahmani, Sarah Diva; Rachman, Imran; Alam, Andi Sahri (Universitas Tadulako, 2018)
Forestry extension workers play a role in changing people's attitudes and behavior so that the community can support forestry development in Indonesia. Tanambulava district, Sigi Regency, the forestry extension workers numbered one person, in contrast to the agriculture extension workers in each village, there were each extension workers. The purpose of this study was to determine the extent of community knowledge about forestry extension activities and how the community's response to forestry extension activities in Tanambulava District, Sigi Regency, Central Sulawesi. This research was conducted in the village of Sibalaya Utara, Tanambulava District, Sigi Regency for 3 months from October to December 2016 through data collection techniques through interviews using a questionnaire with respondents taken based on the consideration that the respondents were village officials (2 people), community leaders (2 people) , traditional leaders (2 people), youth leaders (2 people), General Society (6 people), and farmer groups (26 people) so that the research sample is 40 people. Data analysis using descriptive methods. The results showed the level of knowledge of the community with the activities in the North Sibalaya Village was at the level of lack of knowledge. After explaining the purpose of extension workers for the welfare of the community, they are very responsive and are in the high level category. While the analysis of the data by scaling showed that the community response to forestry extension workers activities was relatively high.